2018
DOI: 10.1007/jhep03(2018)013
|View full text |Cite
|
Sign up to set email alerts
|

Unattainable extended spacetime regions in conformal gravity

Abstract: The Janis-Newman-Winicour metric is a solution of Einstein's gravity minimally coupled to a real massless scalar field. The γ-metric is instead a vacuum solution of Einstein's gravity. Both spacetimes have no horizon and possess a naked singularity at a finite value of the radial coordinate, where curvature invariants diverge and the spacetimes are geodetically incomplete. In this paper, we reconsider these solutions in the framework of conformal gravity and we show that it is possible to solve the spacetime s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Indeed, a finite quantum theory can hide a conformal invariance both at the classical and the quantum level [50,51]. It may be the latter, rather than non-locality itself, that solves the spacetime singularity problem [52,[56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a finite quantum theory can hide a conformal invariance both at the classical and the quantum level [50,51]. It may be the latter, rather than non-locality itself, that solves the spacetime singularity problem [52,[56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…For γ > 1, the singularity is globally naked along equatorial direction, but it is not visible (even locally) along the polar direction. In [36], it was shown that the same singularity at 2M can be resolved in conformal gravity theories. Also it is worth noticing that, the 'Zipoy-Voorhees' metric is non-integrable, as shown in [37], which leads to interesting and possibly chaotic behavior for the general motion of test particles.…”
Section: Introductionmentioning
confidence: 91%
“…[25,26]. The properties of slowly rotating magnetized compact starts [27], and other non-singular spacetime metrics [28] were investigated. In Ref.…”
Section: Introductionmentioning
confidence: 99%